Windblown sand control decision-making support system based on parallel intelligence: Taklimakan desert highway and its sand-breaking system - Fangle CHANG; Mengzhen KANG; Xiujuan WANG; Jiaqiang LEI; Fei-Yue WANG (智能科学与技术学报, 2021)
Using Taklimakan desert highway and its sand-breaking system as the research object for complex system management and control, the ACP-based parallel intelligence theory to deal with the problems of the difficulty in modeling, analyzing, and predicting of sand-breaking system was applied, to realize the intelligent decision support for sand-breaking system management and control, support the sustainable development of aeolian environment.The expert experience knowledge to construct the artificial desert highway sand-breaking system was extracted by simulating physical process.The sand-control efficiency index of the artificial system was calculated using equations, then evaluated and modified by comparing and learning with the actual system.Using parallel intelligent theory, the artificial system and the actual system can learn from each other to provide decision support for sand control.